Volatilitas Harga Emas dan Minyak pada Integrasi Pasar Modal Indonesia dengan Pasar Modal Asia - Sintikhe Mega Treisya; Robiyanto Robiyanto (AFRE (Accounting and Financial Review), 2021)
Capital market integration can be influenced by various variables, such as the volatility of gold and oil prices. The purpose of this study is to analyze the volatility of gold and oil prices on the integration of the Indonesian capital market with the Asian capital market. This study uses secondary data on daily closing prices of gold and oil (West Texas Intermediate and Brent North Sea) along with the Indonesian capital markets (JKSE), Hong Kong (HSI), South Korea (KOSPI), India (NIFTY 50), China (SSEC), Singapore (STI) during the period January 2019 to October 2020. This study uses the DCC-GARCH method to see the dynamic correlation between the capital market, and the GARCH method to analyze the volatility of gold and oil prices on the integration of the Indonesian capital market with the Asian capital market. The results of the study show that there is a positive and negative dynamic correlation between the capital markets, thus proving that the movement of the Indonesian market with other markets tends to vary. The results show that only the volatility of Brent oil has a negative effect on the integration of the Indonesian capital market with the Asian capital market